2019
DOI: 10.1111/jcpt.12838
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin resistance mediated by oxidative stress‐induced 8‐Isoprostaglandin F2

Abstract: Summary What is Known and Objective Aspirin resistance refers to a patient's poor response to aspirin. There are many factors that can contribute to aspirin resistance, including single‐nucleotide polymorphisms, medication compliance, drug‐drug interactions and inflammation. Comment Recently, oxidative stress‐induced 8‐isoprostaglandin F2α has attracted considerable attention because it is considered as a mechanism of aspirin resistance in many diseases, including coronary artery disease, neurology system dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Actin is the primary cytoskeletal component (Chen et al, 2017). In the present study, the actin filament-based process in the GO enrichment function of DEGs was consistent with previous research, which had shown that oxidative stress induced platelet activation by increasing the production of lipid peroxidation (Guo et al, 2019). Meanwhile, oxidative stress lowers platelet nitric oxide, which increases platelet activation and intracellular ROS generation (Manasa and Vani, 2016).…”
Section: Effect Of Oxidative Stress On Platelet Activationsupporting
confidence: 90%
“…Actin is the primary cytoskeletal component (Chen et al, 2017). In the present study, the actin filament-based process in the GO enrichment function of DEGs was consistent with previous research, which had shown that oxidative stress induced platelet activation by increasing the production of lipid peroxidation (Guo et al, 2019). Meanwhile, oxidative stress lowers platelet nitric oxide, which increases platelet activation and intracellular ROS generation (Manasa and Vani, 2016).…”
Section: Effect Of Oxidative Stress On Platelet Activationsupporting
confidence: 90%
“…Under pathological conditions, multiple agonists activating platelets simultaneously could overcome the effect of ASA inhibition on the thromboxane A2 pathway [27] . Furthermore, increased oxidative stress may promote platelet activation and reduce ASA response by producing increased amounts of 8-isoprostagladine F2α [28] . In addition chronic aspirin use has been suggested to cause increased platelet response to thromboxane A2-independent stimuli, such as ADP, thrombin, epinephrine and collagen [29] .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that when ROS generation exceeds the capacity of the antioxidant defense systems and/or in the presence of a reduction of antioxidant enzymes, oxidative stress occurs and represents the primary cause of endothelial dysfunction and vascular damage in metabolic diseases [ 52 ]. A large body of evidence supports the close link between increased oxidative stress, which characterizes both T2DM and HC, and a less-than-expected response to aspirin, with different mechanisms [ 53 ]. Actually, chronic oxidative stress [ 54 ] and decreased antioxidant capacity [ 55 ] have been documented in diabetes but, for the first time, we show plasma SOD as a contributor to promote redox status imbalance and it appears as the only predictor of CEPI PFA-100 in on-aspirin-treated T2DM and primary HC patients.…”
Section: Discussionmentioning
confidence: 99%